Cognitive neuroscience approach to explore the impact of wind turbine noise on various mental functions - Agnieszka Rosciszewska; Maciej Buszkiewicz; Gabriela Dobrzynska-Kobylec; Anna Klichowska; Tomasz Przybyla; Blanka B. Nagy; Andrzej Wicher; Michal Klichowski (Humanities & Social Sciences Communications)
Abstract Despite their alignment with sustainable development principles, wind farms often provoke controversy and misinformation, particularly regarding the noise they produce and their potential impact on human functioning. Concerns have been raised about the possible effects of this noise on irritation levels, psychological well-being, and cognitive functioning. Yet, there is still a lack of controlled, comprehensive studies that could substantiate these concerns. Here, a cognitive neuroscience approach is proposed to experimentally and multifactorial explore wind turbine noise’s impact on various mental functions. We used recordings from an actual wind turbine to investigate its effects on the dynamics of brain waves crucial for complex cognitive tasks, as well as on sustained attention and inductive reasoning in healthy adult volunteers. We also tested the subjective evaluation of the stress induced by wind turbine noise and the annoyance it causes. Control conditions included silence and road traffic noise (participants were blind to the nature of acoustic variables). The findings of this pilot study reveal that short-term exposure to wind turbine noise with a sound pressure level corresponding to the real-world situation (i.e., 65 dB SPL) does not adversely affect any of the examined cognitive functions and is not perceived as more stressful or bothersome than road traffic noise. Furthermore, we utilized various psychological scales and found that even tendencies towards rumination or reduced capacity for reflection and ambiguity tolerance did not lead to maladaptive perceptions of wind turbine noise and, therefore, to a state that might indirectly influence mental functioning. Although these results cannot be generalized, they support the concept that the interlinkage between exposure to wind turbine noise and human cognitive functioning is not a cause-and-effect relationship. We discuss the mediating role of socially constructed beliefs about wind farms in this interrelation. We also indicate how important the use of a cognitive neuroscience approach in future research may be for an objective assessment of the impact of wind farms on human cognition.